Physical simulation of intra-arterial circulation using an experimental bench - O. A. Germanova; V. A. Germanov; Yu. V. Shchukin; A. V. Germanov; A. E. Burmistrov; R. Y. Yusupov; i. O. Prokhorenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The article describes the device and possibilities of application of the original device developed by us for simulation of intra-arterial circulation. The principles of operation of the device, a wide range of experimental and clinical studies in which it can be applied are outlined. The use of this useful model is illustrated by clinical examples.